For a sustainable education in Brazilian Library Science: Diversity in undergraduate courses - Valle, Fernanda; Saldanha, Gustavo (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
The study starts from the global goals of inequality reduction and legal frameworks towards people with disabilities to evaluate curricular components and institutional guidance of active undergraduate courses in Library Science in the southeast area of Brazil. This study, which is of an applied nature, aims to investigate if and how universities offer education oriented to qualification in and towards diversity. The empirical field consists of 22 (twenty-two) courses certified by the Ministry of Education of the Federal Government of Brazil. Once these courses were submitted to documental analysis, we located 13 (thirteen) political-pedagogic projects and 9 (nine) summarized course syllabi to execute the exploratory reading based on keywords related to the inclusion domain and later definition of analytical categories. The reading, analysis, and critical interpretation regarding the results show significant gaps in the librarian education about diversity. Disregarding the predominance of optional courses on Brazilian Sign Language (Libras), the undergraduate courses of the investigated area as an empirical field of this study fail to present, satisfactorily, components or specific objectives aimed toward the learning process of people with disabilities.